2002
DOI: 10.1097/00000542-200211000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Mild Hypothermia Has Minimal Effects on the Tolerance to Severe Progressive Normovolemic Anemia in Swine

Abstract: During progressive normovolemic hemodilution in pigs, hypothermia did not significantly change Hgb(CRIT), but it decreased the Hgb at death, i.e., short-term survival was prolonged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 18 publications
1
10
1
1
Order By: Relevance
“…Consistently, the value of Hb crit in the Roc group (2.4 ± 0.5 g/dl) is comparable to that described in paralyzed animals [13,15,16,17,18,19], while the values of Hb crit obtained in nonparalyzed animals are similar to Hb crit observed in the Sal group [4,12]. …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Consistently, the value of Hb crit in the Roc group (2.4 ± 0.5 g/dl) is comparable to that described in paralyzed animals [13,15,16,17,18,19], while the values of Hb crit obtained in nonparalyzed animals are similar to Hb crit observed in the Sal group [4,12]. …”
Section: Discussionsupporting
confidence: 87%
“…In several experimental studies, a decrease in Hb crit demonstrated that anemia tolerance is increased by (1) hypothermia (moderate reduction of body core temperature reduces total body O 2 demand [16]), (2) hyperoxic ventilation (bioavailability of physically dissolved O 2 is excellent in profound anemia [12,17,18]), (3) infusion of norepinephrine (stabilization of coronary perfusion pressure during hemodilution [13]), and (4) artificial O 2 carriers (maintenance of CaO 2 despite reduced hematocrit [19,20]). In contrast, anemia tolerance is decreased by (1) hypovolemia (reduction of microcirculatory O 2 supply), (2) profound anesthesia (pharmacologic reduction of the cardiac output response to hemodilution [21,22]) and (3) by coronary artery disease (reduced coronary flow reserve [23]).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a reduction of Hb crit could be achieved by hypothermia (moderate reduction of body core temperature reduces total body O 2 demand [18]), infusion of norepinephrine (stabilization of CPP during hemodilution [19]), infusion of artificial O 2 carriers (maintenance of CaO 2 despite reduced hematocrit [20,21]) and continuous NMB (lowering skeletal muscular O 2 demand [22]). …”
Section: Discussionmentioning
confidence: 99%
“…Im Tierexperiment verstarben narkotisierte, hypotherme Schweine bei einer signifikant niedrigeren Hb-Konzentration als normotherme Kontrolltiere [71].…”
Section: Körpertemperaturunclassified